Characterization of phenoloxidase of Penaeus indicus - Anil Kumar, P; Sridhar, N (Indian Journal of Fisheries, 2011)
Quinone-tanned proteins or sclerotinsare important structural proteins of invertebrateexoskeletons. The role of the enzymephenol oxidase in sclerotin formation wasexplained by Pryor (1940 a b) and since thenit has been widely reported in parasites(Mansour 1958, Nellaiappan et al. 1989 a,b), insects (Hackman and Goldberg 1967,Yamazaki 1969, Pau et al. 1971, Brunet1980) and molluscs (Waite and Wilbur1976, Bharati and Ramalingam 1983). InCrustaceans it was studied mainly in crabs(Summers 1967, Vacca and Fingerman 1975,Nellaiappan et al. 1982)